Curative effectiveness of hemoperfusion combined with cinacalcet for bone pain in patients with uremia - LI Yu-zhen; CAO Yong (Linchuang shenzangbing zazhi)
Objective To study the curative effectiveness of hemoperfusion combined with cinacalcet for bone pain in uremia patients. Methods Totally patients with maintenance hemodialysis who were suffered with severe bone pain were randomly divided into group A（ HD group）,group B（ HD + HP group） and group C（ HD + HP + cinacalcet group）. Plasma Ca2+,plasma P3+ and parathyroid hormone（ PTH） were measured pre-dialysis,2 weeks and 6 weeks after treatment.Bone pain was scored. Results Compared with pre-dialysis,the levels of plasma P3+,PTH and the scores of bone pain were significantly lower at 2 nd and 6 th week after treatment in group C（ P <0.05）. There were statistically significant difference in plasma P3+,PTH and scores of bone pain among 3 groups at 6 th week（ P < 0.05）. Conclusions HD + HP + cinacalcet is superior to HD +HP in efficiently clear plasma P3+ and PTH,and relief bone pain,but HD can poorly clear plasma P3+ and PTH,and relief bone pain.